2017
DOI: 10.18844/prosoc.v4i10.3102
|View full text |Cite
|
Sign up to set email alerts
|

Linear programming model for optimum mixing the flour from sieve passages in flour mill industry

Abstract: This study is to design a linear programming model for optimising the mixtures of flour which comes from different sieve passages in flour mill industry. There are different kinds of flour in the market which have different market prices and each has different properties and used for different purposes. The flour obtained from the sieve passages which can be more than 100 in flour milling factories. The characteristics of flour in each sieve passage are different. The main problem is to find out flour mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study demonstrated how a well‐established optimization technique, such as linear programming, can be utilized to efficiently blend flour streams with differing quality, to achieve specific production targets that meet specifications. Others had proposed this technique for flour blending (Avunduk, 2018; Elevli et al., 2017); however, this study demonstrated the advantages of these techniques over conventional blending techniques, such as the use of the sequential cumulative ash curve.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This study demonstrated how a well‐established optimization technique, such as linear programming, can be utilized to efficiently blend flour streams with differing quality, to achieve specific production targets that meet specifications. Others had proposed this technique for flour blending (Avunduk, 2018; Elevli et al., 2017); however, this study demonstrated the advantages of these techniques over conventional blending techniques, such as the use of the sequential cumulative ash curve.…”
Section: Discussionmentioning
confidence: 63%
“…However, most commercial flour mills have more than 20 flour streams. For example, the L.P. modeling conducted by Avunduk (2017) described a flour mill with 64 flour streams. The approach described in this study can be adjusted to suit the number of flour streams by adjusting the number of variables in the model and adjusting the constraints as shown in Equations .0.20.Qt1=false∑i=1SQi10.50.Qt2=false∑i=1SQi20.30.Qt3=false∑i=1SQi3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation